GA3 and BAP on the productivity of clonal mini gardens of Tectona grandis Linn. F - Rodríguez-Solís, Arantxa (2023)
Growth regulators facilitate propagation and increase yield in plant production. Addition in different amounts determines greater effectiveness in cell regeneration. Therefore, this study evaluated the effect of various doses of GA3 (gibberellic acid) and BAP (benzylaminopurine) on the productivity of clonal teak mini gardens in San Carlos, Costa Rica. A trial with a factorial design (2x4) was established. GA3 and BAP were used as factor (A), while doses of 0, 5, 10 and 20 mgl-1 were used as factor (B). The analysis of variance and comparison tests showed that the use of GA3 significantly increased shoot production and shoot length. And BAP had no significant effect on production. The application of 10 and 20 mgl-1 of GA3 increased the production of shoots per mother plant from 1.02 to 1.47 and 1.50 increasing the production by 44 and 47 % respectively, in ordinary biweekly harvest, and 169 to 172 shoots per square meter corresponding to 38 and 33 %. When 5 mgl-1 to 20 mgl-1 of GA3 were applied, shoots from 4.19 to 4.44 cm in length were obtained. In the rooting rate, the differences were presented in GA3 which proved to be superior to BAP by 49% for the average daily rooting, with a rate of 1.30 shoots per day. In conclusion, applying 10 mgl-1 of GA3 is sufficient to increase the productivity performance of clonal teak mini gardens. Keywords: Teak, greenhouse, tree improvement, vegetative propagation, growth regulators.